Emerging Micro and Nanotechnologies - Srivastava, Ruby (IntechOpen, 2020)
Nano-scale technologies is an emerging field of electronics on the scale of a billionth of a meter with integrated mechanical, fluidic, optical, and biological components. These technologies require less space, construction material, less expense, and are easy to transport and store with applications in optical communications, nanocomputing, sensors, and biomedical devices. The electronic applications include silicon photonics, adaptive MEMS, VLSI design and applications, optical tweezers, sensors, and many more. The biological research involves the gene and drug delivery systems for cardiac tissue repair, implantable polymer-based microelectrode arrays, and integrated cell culture systems. This book will give a brief introduction on the continuous revolution of these technologies that have led to renewable energy resources, biophotonics, sensing, cancer cell sorting, and targeted drug delivery applications.